THE INFLUENCE OF FINANCIAL LITERACY AND QUALITY OF FINANCIAL STATEMENTS ON THE PERFORMANCE OF MSMES IN MEDAN MARELAN - Amin Hou (ZILLZELL MEDIA PRIMA, 2023)
This study aims to find out whether financial literacy and the quality of financial reports affect the financial performance of MSMEs in Medan-Marelan in 2023. The method used in this research uses quantitative methods. Furthermore, the data collection technique uses a questionnaire. The data analysis technique uses multiple linear regression analysis with the help of IBM SPSS Software. The research results show that (1). Financial Literacy Affects the Financial Performance of MSMEs in Medan-Marelan City in 2023. The more often financial literacy is carried out by individuals, the better the level of knowledge related to financial management will affect the financial management of a business or activity carried out. (2). The quality of financial reports affects the Financial Performance of MSMEs in Medan-Marelan City in 2023, the better the financial reports prepared by someone, all information will be easily received so that it will affect the financial performance of a business or organization. (3). Financial literacy and quality of financial reports simultaneously affect the Financial Performance of MSMEs in Medan-Marelan City in 2023